Mengasah Keterampilan Sosial Anak di Raudhatul Athfal Alfalah Batusangkar Melalui Program Costum Day - Haryani, Nila; Dadan Suryana (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
This research aims to explore and document the impact of the costume day program on children's social skills in Raudhatul Athfal (RA) Al-falah through a qualitative approach with an ethnographic design. This research uses participant observation methods, in-depth interviews, and content analysis to collect and analyze data from participants involved in the program. The research results revealed that the costume day program positively influenced the development of children's social skills at RA. Al-falah. Through game-based activities and social interaction, children experience improved communication skills, cooperation and building relationships with others. Ethnographic data analysis also highlights changes in children's social interaction patterns, as well as how they integrate the values ​​taught in the costumday program into their daily lives. These findings provide deep insight into how children's experiences in costumday programs can shape their social skills. The implication of this research is to provide an understanding of the impact of the costume day program in RA. Al-falah is carried out through playing while learning and learning while playing. Therefore, this research provides a basis for the development of more effective social skills-based educational strategies in early childhood education institutions